2013
DOI: 10.4012/dmj.2013-065
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the micro-shear bond strength and failure mode of non-enclosed and mold-enclosed luting cements bonded to metal

Abstract: The objective of the study was to compare 1) the mean micro-shear bond strength and 2) failure mode of cements to metals in nonenclosed and mold-enclosed specimens. Specimens were prepared in mold-enclosed and non-enclosed formats from two RMGIC's and a self-adhesive resin-cement. 3-way ANOVA analysis and Tukey post hoc tests were used to compare mean µSBS results (α=0.05). Failure mode was analysed with Pearson's chi-square test (α=0.05). µSBS was significantly affected by the factors substrate and method (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…However, there were no significant differences in failure mode after either the initial shear bond strength or shear fatigue strength tests, and adhesive failures were the most frequently observed type of failure, regardless of the presence or absence of pre‐etching and type of adhesive. This is not surprising, as the bond strength testing was performed using a mold‐enclosed method, which is known to result in an increase in adhesive failures . Previous studies have reported that the bond durability of universal adhesives to phosphoric acid pre‐etched enamel is higher than that to ground enamel, and these findings are consistent with the results in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…However, there were no significant differences in failure mode after either the initial shear bond strength or shear fatigue strength tests, and adhesive failures were the most frequently observed type of failure, regardless of the presence or absence of pre‐etching and type of adhesive. This is not surprising, as the bond strength testing was performed using a mold‐enclosed method, which is known to result in an increase in adhesive failures . Previous studies have reported that the bond durability of universal adhesives to phosphoric acid pre‐etched enamel is higher than that to ground enamel, and these findings are consistent with the results in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the shear load was applied directly to metal rings enclosing the resin composite bonded to dentin. It has been reported that metal mold‐enclosed bonding specimens exhibit a higher frequency of adhesive failure than do non‐metal mold‐enclosed bonding specimens . This may be one of the reasons why adhesive failures predominated, regardless of the type of resin composite in this study.…”
Section: Discussionmentioning
confidence: 59%
“…In the present study, the shear load was applied to the metal rings enclosing the resin composite bonded to dentin, and adhesive failures were observed most frequently, regardless of the type of adhesive. This can be explained by the fact that bonding specimens enclosed within a metal mold exhibit a higher frequency of adhesive failure than do unenclosed specimens . A previous study has stated that an increased incidence of adhesive failure in bond strength tests is desirable to provide more relevant information about the mean bond strength .…”
Section: Discussionmentioning
confidence: 99%